2006
DOI: 10.1063/1.2339044
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on switching kinetics of three-dimensional ferroelectric capacitor arrays

Abstract: Articles you may be interested inMultilevel recording in Bi-deficient Pt/BFO/SRO heterostructures based on ferroelectric resistive switching targeting high-density information storage in nonvolatile memories Appl. Phys. Lett. 103, 263502 (2013); 10.1063/1.4855155 Polarization behavior of poly(vinylidene fluoride-trifluoroethylene) copolymer ferroelectric thin film capacitors for nonvolatile memory application in flexible electronics J. Appl. Phys. 108, 094102 (2010); 10.1063/1.3500428 Spatial variations in loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Imprint could result from elevated temperatures due to asymmetric migration of species along the film, exposure to UV light or x-rays 17 as well as asymmetric film-electrode top and bottom interfaces. 18 While the exact mechanisms of imprint are not known, there is strong experimental evidence that it results from trapped charges, charged defects, and other possible defect dipole complexes, surface fields, and stress gradients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imprint could result from elevated temperatures due to asymmetric migration of species along the film, exposure to UV light or x-rays 17 as well as asymmetric film-electrode top and bottom interfaces. 18 While the exact mechanisms of imprint are not known, there is strong experimental evidence that it results from trapped charges, charged defects, and other possible defect dipole complexes, surface fields, and stress gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition conditions of thin film materials are often far from ideal and hence kinetic factors play an important role in the ultimate stoichiometry of the film. [18][19][20][21] As perovskite FEs have a mix of ionic and covalent interatomic bonding, local deviations from the exact stoichiometry can create frozen dipoles and electrostatic fields emanating from these complexes. Furthermore, it has often been discussed that these "defects" can then trap carriers and become p-or n-type centers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently, intensive experimental research works have been carried out to investigate radiation effects on ferroelectric thin films and ferroelectric-based devices. [5][6][7][8][9][10][11] Good application potentials of ferroelectrics in highly reliable and radiation-hardened memories were reported in these works. Although the remanent polarization was found much more robust than the floating gate stored charge, 11) radiation-induced degradations (e.g., polarization loss, fatigue, and imprint) in ferroelectric thin films were still observed.…”
mentioning
confidence: 84%
“…Recently, intensive experimental research has been performed to investigate the radiation effect of ferroelectric thin films. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example, Menou et al 8 had demonstrated that the electrical characteristics of Pt/SrBi 2 Ta 2 O 9 (SBT)/Pt ferroelectric capacitor changed significantly during or after irradiation. In their work, both "fatigue-like" (polarization reduction) and/or "imprint-like" (voltage shift) phenomena were observed.…”
mentioning
confidence: 99%
“…In their work, both "fatigue-like" (polarization reduction) and/or "imprint-like" (voltage shift) phenomena were observed. Then, Courtade et al 10 showed that high dose of x rays can accelerate fatigue-like and/or imprint mechanisms that may perturb normal "written" or "writing" operations in memory. Later, Petrov et al 13 indicated that a certain wavelength of ultraviolet radiation can induce significant leakage current in Ba 0.3 Sr 0.7 TiO 3 thin film capacitors.…”
mentioning
confidence: 99%